Examining the impact of oil use on the relationship between GDP growth and life expectancy in Malaysia - Mohd Shahidan Shaari; Amri Sulong; Zulkefly Abdul Karim; Abdul Rahim Ridzuan; Miguel Angel Esquivias; Ehsan Ullah (Discover Sustainability)
Abstract Life expectancy reflects a population's overall health and prosperity. This study applies the Auto-Regressive Distributed Lag (ARDL) method to analyze how oil use influences the link between GDP growth and life expectancy in Malaysia from 1980 to 2020. The results show that while GDP growth boosts life expectancy in both the short and long term, dependence on oil negatively affects it. Wealth accumulation positively contributes to longevity, whereas healthcare budget distribution surprisingly reduces life expectancy. These findings highlight the complex relationship between economic development and environmental conditions, suggesting the need for policies that support both growth and environmental sustainability to improve public health outcomes.